1997
DOI: 10.1046/j.1365-2818.1997.1960757.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate aggregates resulting in the interaction of bile salt with liposomes studied by transmission electron microscopy and light scattering techniques

Abstract: SummaryThe interaction of sodium cholate (SC) with phosphatidylcholine liposomes was studied by means of transmission electron microscopy (TEM), changes in the mean particle size (quasielastic light scattering, QELS) and in the static light scattering (SLS) of the system during liposome solubilization. A good correlation was found between the TEM diameter of particles and the mean hydrodynamic diameter (HD) determined by QELS. The intermediate aggregates resulting in this interaction were dependent on the SC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…It has been previously demonstrated that the TEM technique applied to negatively stained vesicles is an appropriate method to study the formation and morphology of vesicular structure (Delamaza et al. 1997; van Zanten and Zasadzinski 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously demonstrated that the TEM technique applied to negatively stained vesicles is an appropriate method to study the formation and morphology of vesicular structure (Delamaza et al. 1997; van Zanten and Zasadzinski 2005).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously demonstrated that the TEM technique applied to negatively stained vesicles is an appropriate method to study the formation and morphology of vesicular structure (Delamaza et al 1997;van Zanten and Zasadzinski 2005). Microstructures of the vesicle are readily visualizable owing to their high electron density, but negative staining with uranyl acetate is performed to enhance image quality.…”
Section: Tem Micrograph Of the Liposomesmentioning
confidence: 99%
“…Moreover, a comparison of LB-I incubated in PBS containing urea in the presence and absence of sodium deoxycholate showed that liposomes were more elongated in presence of sodium deoxycholate, further suggesting a higher flexibility (and thus, permeability) of LB-I under these conditions, as reported in literature. [55] The possibility to fabricate enzyme-encapsulated nanomotors which motion is activated under certain conditions opens new avenues for using this class of nanomotors in conditions in which the enzymes can degrade. As proof-of-concept, we evaluated whether the liposomal chassis can be used to protect the enzymes when crossing adverse conditions, making them still active when the motion triggering conditions are found or applied.…”
Section: (4 Of 8)mentioning
confidence: 99%
“…For comparison purposes, we also synthesized a second prototype of LBs, LipoBots-Outside (LB-O), in which the urease enzymes are attached to the liposomes' surface by physisorption. [54] This salt acts as an edge activator, causing disruption and permeabilization of the lipid bilayer [55][56][57] and therefore, enabling exchange of substrates and products. Accordingly, exposure of LB-I to sodium deoxycholate triggers motion of the nanomotor.…”
Section: Introductionmentioning
confidence: 99%
“…calorimetry [20][21][22][23][24], neutron scattering [25][26][27], X-ray diffraction [28], spectroscopy [29,30]; and several other biophysical techniques. The determination of partition coefficients of amphiphilic molecules for partitioning between aqueous and lipid phase is of fundamental importance for a quantitative interpretation of lipid-surfactant interactions and provides the basis for the understanding of the intermolecular interaction energies.…”
Section: Introductionmentioning
confidence: 99%